Pengaruh Dana Desa dan Status Desa terhadap Penanganan Stunting di Kabupaten Pesisir Selatan - Hayati, Isra; Taifur, Werry Darta (Jurnal Informatika Ekonomi Bisnis, 2024)
This study aims to analyze the influence of the Village Fund and Village Status on stunting in Pesisir Selatan Regency. Using a quantitative approach with multiple regression methods, this study measures how Village Fund allocations and village status contribute to reducing stunting rates. Data was collected through documentation study techniques from relevant agencies and processed to ensure statistical assumptions such as normality, multicollinearity, and homoscedasticity were met. The results show that the Village Fund has no influence on stunting reduction, while the IDM shows a significant influence. This indicates that budget allocations directed towards health and nutrition programs do not have a direct impact on stunting reduction compared to general village infrastructure improvements. This conclusion emphasizes the importance of prioritizing allocations. These results indicate that even if a village achieves progress in terms of infrastructure, economy, and public facilities, it can still reduce the problem of stunting.This study also suggests expanding the scope of variables in the future to enrich the understanding of the factors that affect stunting more comprehensively.